Deep brain stimulation of the subthalamic nucleus alters frontal activity during spatial working memory maintenance of patients with Parkinson's disease. Issue 4 (3rd July 2016) - Mayer, Jutta S.; Neimat, Joseph; Folley, Bradley S.; Bourne, Sarah K.; Konrad, Peter E.; Charles, David; Park, Sohee
ABSTRACT: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) improves the motor symptoms of Parkinson's disease (PD). The STN may represent an important relay station not only in the motor but also the associative cortico-striato-thalamocortical pathway. Therefore, STN stimulation may alter cognitive functions, such as working memory (WM). We examined cortical effects of STN-DBS on WM in early PD patients using functional near-infrared spectroscopy. The effects of dopaminergic medication on WM were also examined. Lateral frontal activity during WM maintenance was greater when patients were taking dopaminergic medication. STN-DBS led to a trend-level worsening of WM performance, accompanied by increased lateral frontal activity during WM maintenance. These findings suggest that STN-DBS in PD might lead to functional modifications of the basal ganglia-thalamocortical pathway during WM maintenance.